Does the Position of the Paramedic Performing Chest Compressions During a Simulated Cardiac Arrest Influence Compliance With the 2010 Guidelines? - Davey, P; Whatman, C; Dicker, B (New Zealand Resuscitation Council, 2014)
No abstract.